Diasporic Space: a Site of Contestation and Reconciliation in Interpreter of Maladies and The Middleman and Other Stories - Khanal, Niran (Literary Studies, 2016)
This paper explores the space of diaspora in Jhumpa Lahiri’s Interpreter of Maladies and Bharati Mukherjee’s The Middleman and Other Stories. Both the authors present diasporic context, in which the immigrants hold an in-between space between home and host. The expatriates maintain emotional ties with the country of their origin resisting assimilation into the structure of the host society. Diasporic societies present the individuals with the challenge of balancing a dual orientation: acculturation into an alien culture and attachment for the home culture. Such a condition of dual orientation is the problem for research. The research attempts to answer this question: how the location of diaspora ̶ a third space ̶ is formed and what is the impact of dialectics between home and host on the lives of the diasporic people, and how they negotiate between incompatible elements to shape this third space. The growing trend of diaspora, a phenomenon of global migration, and its impact on established relations needs academic attention. The paper contextualizes the theoretical concept of diaspora in fictional representations. It adopts the modern theoretical concepts of diaspora and contextualizes them in Interpreter of Maladies and The Middleman and Other Stories. The dialectical relation between the host and home world shapes an in-between space which comes into existence through reconciliation between two different forces.